A critical humanist intervention: agency, structure and values - Arukia izabel (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The main aim of the article is to suggest what and how a contemporary and revised version of humanism, inflected with critical realism and Marxism, can contribute to sociology. I mainly focus on two areas in which sociology is often lacking today: theorizing the relationship between structure and agency, and deciding what to do with moral evaluations in sociological analyses. I submit that the solution for both lies in trying finally to transcend the traditionally hostile and mutually exclusive paradigms of "humanist" or "cultural" Marxism on the one hand and "anti-humanist" or "scientific" Marxism on the other. This allows us to carefully re-establish the agency of human subjects and the moral dimension, both of which were and continue to be dismissed by anti-humanist or post-humanist social science, without neglecting the objective and causally relevant existence of social structures at the same time